2006
DOI: 10.1016/j.landurbplan.2005.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Urban land classification and its uncertainties using principal component and cluster analyses: A case study for the UK West Midlands

Abstract: An urban land-cover classification of the 900 km 2 comprising the UK West Midland metropolitan area was generated for the purpose of facilitating stratified environmental survey and sampling. The classification grouped the 900 km 2 into eight urban land-cover classes. Input data to the classification algorithms were derived from spatial land-cover data obtained from the UK Centre for Ecology and Hydrology, and from the UK Ordnance Survey. These data provided a description of each km 2 in terms of the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…For this study, we selected 30 ponds that hold water for at least four consecutive months of the year, between 2 m 2 and Fig. 1 Geographic location of 30 study ponds (circles) in the West Midland conurbation, UK Sites are shown in relation to land-use within 1 km squares, using the classification of Owen et al (2006). Pond types were established using a Ward's hierarchical clustering procedure 20,000 m 2 (2 ha) in surface area (Pond Conservation Group 1993) from 1023 possible sites identified using a ArcGIS 9.3 Geographical Information System (GIS).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we selected 30 ponds that hold water for at least four consecutive months of the year, between 2 m 2 and Fig. 1 Geographic location of 30 study ponds (circles) in the West Midland conurbation, UK Sites are shown in relation to land-use within 1 km squares, using the classification of Owen et al (2006). Pond types were established using a Ward's hierarchical clustering procedure 20,000 m 2 (2 ha) in surface area (Pond Conservation Group 1993) from 1023 possible sites identified using a ArcGIS 9.3 Geographical Information System (GIS).…”
Section: Study Areamentioning
confidence: 99%
“…Pond types were established using a Ward's hierarchical clustering procedure 20,000 m 2 (2 ha) in surface area (Pond Conservation Group 1993) from 1023 possible sites identified using a ArcGIS 9.3 Geographical Information System (GIS). Site selection was stratified across a gradient of eight urban land-use classes from rural villages to heavily urbanised city centres, characteristic of the West Midlands (Owen et al 2006, Fig. 1).…”
Section: Study Areamentioning
confidence: 99%
“…Cluster analysis encompasses different algorithms and methods for grouping similar objects into respective categories (Owen et al 2006). In this study, the Euclidean distance (Eq.…”
Section: Classification Of Urbanization Levelsmentioning
confidence: 99%
“…It uses data from OS and the UK Center for Ecology and Hydrology (CEH) classified by a principle component analysis and cluster analysis [32]. The classification scheme was based on 27 different input attributes and the output spatial resolution is a 1 km 2 grid showing similar urban land morphology (for more details see [32]). The result map of this approach is shown in Fig.5, which consists of eight categories urban land use classification derived per pixel based on their common land use.…”
Section: Fig4 Urban Atlas Of Land Use Adopted From [21]mentioning
confidence: 99%